Vaccinations and Dravet Syndrome - Christian M. Korff (Pediatric Neurology Briefs Publishers, 2015)
Investigators from various university hospitals, reference medical institutions and epilepsy centers, and the national institute for public health and environment in the Netherlands, studied the effect of vaccinations on seizure risk and disease course in patients with Dravet syndrome (DS).